Peningkatan Aktivitas dan Hasil Belajar Materi Sistem Ekskresi Melalui Inkuiri Terbimbing Pada Siswa SMP Negeri 1 Kemalang - Titiek Prasetyowati; Tri Wiharti; Anwari Adi Nugroho (Universitas Veteran Bangun Nusantara Sukoharjo, 2020)
This study aimed to improve the learning outcomes of class VIII E students of SMP Negeri 1 Kemalang in the 2018 2019 academic year using the Guided Inquiry learning model. This research was a class action research consisting of 2 cycles. Each cycle consists of planning. observation and reflection. Data were taken from students who were the subject of research. The technique of collecting data using observations, written tests and documentation. The data analysis technique used comparative descriptive. The results showed that study stated at the first cycle of student activity were 67% and learning completeness was 73%. In cycle II, student activity was 80 %. Already met the performance indicators ≥75% of students achieved high activity criteria (≥ 75%). Classical completeness increased by 87%, it has met the performance indicator, namely ≥ 85%. So it can be concluded that the guided inquiry learning model can improve student learning outcomes. Keywords: learning activities, learning outcomes, guided inquiry